The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jgh.15364
|View full text |Cite
|
Sign up to set email alerts
|

Increasing changes in visceral adiposity is associated with higher risk for colorectal adenoma: Multilevel analysis in a prospective cohort

Abstract: Moon was involved in the acquisition of data, analysis and interpretation of data, and drafting of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Excessive fat beyond the capacity of SAT is stored in ectopic fat, the so-called VAT [ 35 ]. However, in terms of colonic adenomas, SAT was not a significant risk factor for colonic adenoma in previous studies [ 13 , 14 , 36 ]. Previous studies have reported that SAT correlates with fat mass measured using BIA.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Excessive fat beyond the capacity of SAT is stored in ectopic fat, the so-called VAT [ 35 ]. However, in terms of colonic adenomas, SAT was not a significant risk factor for colonic adenoma in previous studies [ 13 , 14 , 36 ]. Previous studies have reported that SAT correlates with fat mass measured using BIA.…”
Section: Discussionmentioning
confidence: 66%
“…VFA measured using computed tomography (CT) scans has been widely studied and shown to have a positive relationship with adenomas [ 13 ]. In a longitudinal study, increased VFA increased both incident and recurrent colorectal adenomas [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the association between VAT and CRC was controversial, its association with colorectal polyp was quite well established [ 31 , 32 ]. Various studies have demonstrated that increase in VAT area was an independent risk factor for colorectal polyp [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed that increase in visceral adiposity was associated with a higher risk for CRA, indicating there might also be changes in the severity of NAFLD. 5 We propose that severity of NAFLD and onset time of first diagnosis could be reported to better explain the conclusion.…”
mentioning
confidence: 86%